2013
DOI: 10.1007/s00262-013-1400-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel adenoviral vector induces T-cell responses despite anti-adenoviral neutralizing antibodies in colorectal cancer patients

Abstract: First generation, E1-deleted Adenovirus subtype 5 (Ad5)-based vectors, although promising platforms for use as cancer vaccines, are impeded in activity by naturally occurring or induced Ad-specific neutralizing antibodies. Ad5-based vectors with deletions of the E1 and the E2b regions (Ad5 [E1-, E2b-]), the latter encoding the DNA polymerase and the pre-terminal protein, by virtue of diminished late phase viral protein expression, were hypothesized to avoid immunological clearance and induce more potent immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 43 publications
4
83
0
Order By: Relevance
“…by engineered adenoviruses, which are capable of safely vaccinating and re-vaccinating against hundreds of neoepitopes and tumor-associated antigens despite pre-existing immunity against adenovirus [47]. Remarkable results have thus far been published demonstrating the delivery of tumor-associated antigens by this engineered adenovirus in a cohort of late-stage colorectal cancer patients [48].…”
Section: Discussionmentioning
confidence: 93%
“…by engineered adenoviruses, which are capable of safely vaccinating and re-vaccinating against hundreds of neoepitopes and tumor-associated antigens despite pre-existing immunity against adenovirus [47]. Remarkable results have thus far been published demonstrating the delivery of tumor-associated antigens by this engineered adenovirus in a cohort of late-stage colorectal cancer patients [48].…”
Section: Discussionmentioning
confidence: 93%
“…While this may serve as a partial contributor toward these divergent responses, multiple recombinant Ad5 studies have shown that anti-Ad5 immunity alone is not predictive of a recombinant Ad5-based vaccine's efficacy (11,14,47).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional Ad5[E1ÏȘ] vaccines possess the ability to promote strong immunologic responses against their expressed transgenes, but the same properties also trigger host antiviral responses, which can lead to increased toxicity, limited persistence, and decreased efficacy in the face of preexisting anti-Ad5 immunity (7,28,29,34,46 (28,34), and remain therapeutically efficacious in hosts harboring substantial preexisting anti-Ad5 immunity (5,(14)(15)(16)30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, CEA has been investigated extensively as an immunotherapeutic target for colorectal and various other cancers [Turriziani et al 2012]. In a phase I/II clinical trial, treatment with an adenoviral gene delivery platform encoding the CEA antigen produced cell-mediated immunity in 61% of patients with advanced CRC and a 48% OS rate at 12 months [Morse et al 2013a]. A phase II study in CRC patients who were disease-free following metastasectomy and perioperative chemotherapy compared the effectiveness of autologous dendritic cells modified with PANVACℱ, a poxvector encoding both CEA and MUC1, to the PANVACℱ poxvector administered in combination with GM-CSF.…”
Section: Oncofetal Antigens: Cea and 5t4mentioning
confidence: 99%